The validity and reliability of the Stoma Self‐Efficacy Scale: A methodological study - Karaçay, Pelin; Yigitoglu, Eylem Toğluk; Karadağ, Ayişe (International journal of nursing practice, 2020)
Aims To assess the validity and reliability of the stoma self‐efficacy scale for Turkish‐speaking individuals with stoma. Background Self‐efficacy in stoma care is one of the most important variables requiring compliance for an increase in the quality of life and well‐being of individuals with stoma. Design A methodological study. Methods This study used translation and back translation for the scale's language equivalence and expert opinion for the content validity. An expert panel and 10 individuals with stoma evaluated the scale for face validity. The scale's reliability was assessed by internal consistency, Pearson correlation, and test–retest reliability in a sample of 174 individuals with stomas. The scale's construct validity was tested with confirmatory factor analysis and exploratory factor analysis. Results The content validity index was .96, and Cronbach's alpha was .95. In the test–retest analysis, the intraclass correlation coefficients were high. In the factor analysis, two factors emerged from the scale, and after the confirmatory factor analysis and scale modification, the fit indices of the model were found to provide a good level of validity. Conclusion The Turkish version of the stoma self‐efficacy scale is a valid and reliable tool to determine the levels of self‐efficacy in individuals with stoma. SUMMARY STATEMENT What is already known about this topic? Stoma creation is one of the most common surgical interventions. The ability to cope with the psychological, physiological and sociocultural changes experienced by individuals with stoma after surgery is related to their levels of self‐efficacy. Valid and reliable instruments are needed to determine the levels of self‐efficacy of individuals with stoma. What this paper adds? The Turkish version of the stoma self‐efficacy scale is a valid and reliable tool to determine the levels of self‐efficacy in individuals with stoma. The stoma self‐efficacy scale can be used by nurses to evaluate the self‐efficacy levels of Turkish‐speaking individuals with stoma in any part of the world. The implications of this paper: The stoma self‐efficacy scale can be used to evaluate self‐efficacy levels in individuals with stoma and for respective research. The adaptation of the stoma self‐efficacy scale into Turkish may contribute to the dissemination of self‐efficacy results of Turkish individuals with stoma internationally and to the comparative literature.